New Metal Complexes of Thiosemicarbazone Mannich base Ligand; Synthesis, Structural Characterisation and Biological Activity - Enaam Ismail Yousif, Nihad Kadhum Hasan, Mohamad J. Al-Jeboori (Pakistan Journal of Medical & Health Sciences, 2022)
The synthesis of a new tridentate Schiff-base thiosemicarbazone ligand (HL) that derived from the reaction of ((R)-2-((4-(dimethylamino)phenyl)((2-nitrophenyl)amino)methyl)-5,5-di methyl- cyclohexane-1,3-dione with thiosemicarbazide is reported. The reaction of the title ligand(E)-2-((R)-2-((R)-(4-(dimethylamino)phenyl)((2-nitrophenyl)amino)methyl)-5,5-dimethyl-3-oxocyclohexylidene)hydrazine-1-carbothioamide with selected metal ions of Co(II), Ni(II), Cu(II), Zn(II) and Cd(II) gave the title monomeric complexes. Analytical and spectroscopic techniques were used, as required, to characterise the prepared compounds. These include; elemental microanalysis, 1H, 13C-NMR and mass spectra, FT-IR and electronic spectra, magnetic susceptibility and conductance. These analyses revealed the formation of monomeric complexes of octahedral arrangement about Co(II); Cu(II) and square planar and tetrahedral geometry with the Ni(II) and Zn(II); Cd(II)) ions, respectively. Thermal stability (TGA-DSC) of HL and selected complexes were also explored. The antimicrobial activity of the title compounds (ligand and complexes) towards several microorganism (bacteria and fungi species) were examined. The collected data revealed the antimicrobial activity of the ligand was enhanced upon complex formation. Keywords: Thiosemicarbazone ligand, Metal complexes, Structural investigation, Thermal stability, Antimicrobial activity.